Foraging in Urban Environments Increases Bactericidal Capacity in Plasma and Decreases Corticosterone Concentrations in White Ibises - Cummings, Caroline R.; Khan, Nicola Y.; Murray, Maureen M.; Ellison, Taylor; Welch, Catharine N.; Hernandez, Sonia M.; Navara, Kristen J. (Frontiers in Ecology and Evolution, 2020)
As humans continue to infringe on natural habitats, more animals are exposed to urban habitats and associated challenges. It is still unclear, however, whether the movement of animals into urban habitats negatively influences the health and/or survival of those animals, however those animals often experience shifts in resource availability, diet composition, and exposure to stimuli that are new and potentially stressful. Recently, white ibises (Eudocimus albus) have become increasingly common in urban habitats where they forage in close proximity to humans and even interact with them, collecting food handouts. We hypothesized that foraging in urban habitats would negatively impact measures of health, impair innate immunity, trigger elevated concentrations of corticosterone, and depress physiological responses to stressors in white ibises. We found that birds captured from urban sites had lower ectoparasite scores and higher bactericidal capacity against Escherichia coli than those captured in natural sites. Additionally, adults captured in urban habitats had a significantly lower baseline corticosterone concentrations during the post-breeding season, and corticosterone responses to a handling challenge were lower for birds captured from urban sites during year 2 of the study. These results indicate that exposure to urban habitats impacts ibis health, though in the opposite direction of what was predicted.